Ferric nitrate-catalyzed aerobic oxidative ring-opening of substituted furans for the stereoselective synthesis of (Z)-1,4-enediones - Tao Ye; Na Lin; Jia-Huan Shen; Lichun Kong; Yang-Zi Liu; Quannan Wang; Wei-Ping Deng (Green Synthesis and Catalysis)
A simple and highly efficient catalytic system for the selective aerobic oxidative ring-opening of substituted furans has been achieved using Fe(NO3)3·9H2O as a catalyst and air as an oxidant under mild conditions. A series of (Z)-1,4-enediones were obtained in good yields (up to 97 %) with excellent stereoselectivity (up to ​> ​20:1 Z/E ratio). The present synthetic method exhibits perfect atom economy, wide substrate scope, and highly functionalized products allowing diverse transformations.